Antecedent Factors in Achieving Marketing Student Performance with a Career Construction Theory Approach: Antecedent Factors in Achieving Marketing Student Performance with a Career Construction Theory Approach - Hartono, Hartono; Andi Setiawan; Subandi, Subandi; M. Nahar; Sri Astuti (International journal of technology and education research, 2023)
Career Construction Theory strengthens this research effort to build a model that can be a lever for improving Marketing Student Performance in higher education. Marketing Student Employability is developed as an intervening variable that bridges medically between variables with Marketing Student Performance. The study believes students still need the right hard and soft skills to deal with uncertainty with the certainty of dynamic labor market demand. This study obtained interval data from the answers of 225 respondents using a survey questionnaire with an interval scale of 1-10. Testing with AMOS 25.0 was selected in this study to test the feasibility of the model and hypothesis. The results of structural modeling show that testing of hypothesis 4 obtained specific soft-skill marketing results that are significantly unrelated to marketing student employability.